Revisiting I-BAR Proteins at Central Synapses - Chatzi, Christina; Westbrook, Gary L. (Frontiers in Neural Circuits, 2021)
Dendritic spines, the distinctive postsynaptic feature of central nervous system (CNS) excitatory synapses, have been studied extensively as electrical and chemical compartments, as well as scaffolds for receptor cycling and positioning of signaling molecules (1). The dynamics of the shape, number, and molecular composition of spines, and how they are regulated by neural activity, are critically important in synaptic efficacy, plasticity, and ultimately learning and memory (2). Dendritic spines originate as outward protrusions of the cell membrane, but this aspect of spine formation and stabilization has not been a major focus of investigation compared to studies of membrane protrusions in non-neuronal cells. We review here one family of proteins involved in membrane curvature at synapses, the BAR (Bin-Ampiphysin-Rvs) domain proteins. The subfamily of inverse BAR (I-BAR) proteins sense and introduce outward membrane curvature, and serve as bridges between the cell membrane and the cytoskeleton. We focus on three I-BAR domain proteins that are expressed in the central nervous system: Mtss2, MIM, and IRSp53 that promote negative, concave curvature based on their ability to self-associate. Recent studies suggest that each have distinct functions in synapse formation and synaptic plasticity. The action of I-BARs is also shaped by crosstalk with other signaling components and possibly by heterooligomerization with other family members, forming signaling platforms that can function in a circuit-dependent manner. Understanding the spatiotemporal resolution of synaptic I-BAR protein expression and their interactions should provide insights in the interplay between activity-dependent neural plasticity and network rewiring in the CNS.